2010
DOI: 10.1007/s10637-010-9430-6
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal-related compound-induced cell growth suppression and apoptosis in the chronic myelogenous leukemia K562 cell line

Abstract: Liquid crystals are the state of matter existing between the liquid and the crystalline phase, and there is a recent surging interest in its biological effects. Our previous study showed that liquid crystal-related compounds (LCRCs), which are precursors of the liquid crystal, enhanced hematopoietic differentiation at a relatively low concentration (Biol Pharm Bull, 32, 2009). However, biological potentials of LCRCs on tumor cells are unclear. In this study, the biological activity of 16 LCRCs to a chronic mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In the present study, we demonstrated that LCRCs possessing three aromatic rings, whose potential to induce apoptosis had been previously demonstrated in human chronic myelogenous leukemia K562 cells (12), suppressed cell growth in human non-small cell lung cancer A549 cells ( Fig. 2A).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In the present study, we demonstrated that LCRCs possessing three aromatic rings, whose potential to induce apoptosis had been previously demonstrated in human chronic myelogenous leukemia K562 cells (12), suppressed cell growth in human non-small cell lung cancer A549 cells ( Fig. 2A).…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, c-Jun N terminal kinase (JNK) is involved in not only apoptosis but also cell cycle arrest (19). Furthermore, since Fukushi et al reported that LCRC-1 activated JNK in the K562 cells (12), there is a possibility that JNK is associated with suppression of LCRC-1 in the A549 cells. However, a JNK inhibitor VIII (Calbiochem ® ) did not affect cell suppression by LCRC-1 in the A549 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this interest, four compounds were evaluated for their anti-cancer function: 2-(4-butoxyphenyl)-5-(4-hydroxyphenyl)pyrimidine (LC1), 2-{4-(4-hexyloxyphenyl)phenyl}-5-hydroxypyrimidine (LC2), 4′-[(6-hydroxyhexyl)oxy]-[1,1′-biphenyl]-4-carbonitrile (LC3), and 4-(4-(5-octylpyridin-2-yl)phenoxyl)butan-1-ol (LC4). These LCs showed marked cell growth suppression, cell cycle arrest at the G2/M phase, and apoptosis [ 121 , 129 , 130 , 131 , 132 , 133 , 134 ]. Chronic myelogenous leukemia K562 cells, A549 human lung cancer cells, and U937 human leukemic monocyte lymphoma cells were used to test LCs anti-cancer properties by evaluating cell growth, cell cycle distribution, and signaling pathways using flow cytometry and Western blot analysis.…”
Section: Liquid Crystal Chemotherapeutic Drugs For the Treatment Omentioning
confidence: 99%
“…Both LC1 and LC2 showed cell growth suppression in K562 cells at a treatment in the µM range. The suppressive effects can be related to the specific chemical structures of LC1 and LC2 [ 133 ]. LC1 and LC2 both consist of a core of three aromatic rings (pyrimidine ring with one alkyl chain and one hydroxide on either side).…”
Section: Lc1 and Lc2 Suppressive Effects On K562 Cell Growthmentioning
confidence: 99%